An Action Research on Teaching Addition and Subtraction to an Illiterate Student with Dyscalculia - Beyza Koç; İsa Korkmaz (Anı Publishing, 2019)
In this study, it is aimed to teach the addition and subtraction processes to an illiterate student who attend 3rd grade at elemantary school and who has dyscalculia. In this study the researcher and the illiterate student, who was attending 3rd grade and has report on dyscalculia worked together as an indivudialized education athmoshere. First of all, in the prepared program, student was subjected to pretest to measure about his level of the subject. An illiterate student was selected according to the prerequisite skills that did not know how to read, writing and recognize the concept of amount and size and, step value concepts, adding and subtracting processes in mathematics. The instruction was carried out in a room in the school, with a time of 40 minutes per day (one lesson) in the form of individual instruction with illiterate student. In addition, the study was supported by a researcher-developed scenario booklet, concrete materials, computer games, prizes, and assignments. Action research from qualitative research methods has been adopted in the study. The data were analyzed using descriptive analysis technique. After learning the method of collecting with the help of a scenario developed by the researcher, it was determined that student achieved more than 90 % on teaching basic addition process and subtraction process. Gains have been actualized by an illiterate student with math learning difficulties with over 90 % success in 63 lessons. Social validity data were collected through observation and interviews to identify strengths or weaknesses and changes occurring in student work. As a result of the studies, it has been determined that the student gain self-confidence by enjoying her sense of accomplishment.